Unparalleled coupled ocean-atmosphere summer heatwaves in the New Zealand region: drivers, mechanisms and impacts - Salinger, M. James; Diamond, Howard J.; Behrens, Erik; Fernandez, Denise; Fitzharris, B. Blair; Herold, Nicholas; Johnstone, Paul; Kerckhoffs, Huub; Mullan, A. Brett; Parker, Amber K.; Renwick, James; Scofield, Claire; et al. (Climatic change, 2020)
During austral summers (DJF) 1934/35, 2017/18 and 2018/19, the New Zealand (NZ) region (approximately 4 million km 2 ) experienced the most intense coupled ocean-atmosphere heatwaves on record. Average air temperature anomalies over land were + 1.7 to 2.1 °C while sea surface temperatures (SST) were 1.2 to 1.9 °C above average. All three heatwaves exhibited maximum SST anomalies west of the South Island of NZ. Atmospheric circulation anomalies showed a pattern of blocking centred over the Tasman Sea extending south-east of NZ, accompanied by strongly positive Southern Annular Mode conditions, and reduced trough activity over NZ. Rapid melt of seasonal snow occurred in all three cases. For the two most recent events, combined ice loss in the Southern Alps was estimated at 8.9 km 3 (22% of the 2017 volume). Sauvignon blanc and Pinot noir wine grapes had above average berry number and bunch mass in 2018 but were below average in 2019. Summerfruit harvest (cherries and apricots) was 14 and 2 days ahead of normal in 2017/18 and 2018/19 respectively. Spring wheat simulations suggested earlier flowering and lower grain yields compared to average, and below-average yield and tuber quality in potatoes crops occurred. Major species disruption occurred in marine ecosystems. Hindcasts indicate that the heatwaves were either atmospherically driven or arose from combinations of atmospheric surface warming and oceanic heat advection.